2000
DOI: 10.1215/03616878-25-4-623
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Reform, Substance Use, and Mental Health

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 50 publications
7
130
1
Order By: Relevance
“…Mounting evidence suggests that welfare recipients have significantly higher rates of psychiatric disorders than their non-welfare counterparts , and that substance abuse is at least as prevalent among welfare recipients as non-recipients (Jayakody, Danziger, and Pollack, 2000;Jayakody and Stauffer, 2000). When present, mental health disorders and/or substance abuse problems affect the employment outcomes of welfare recipients .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence suggests that welfare recipients have significantly higher rates of psychiatric disorders than their non-welfare counterparts , and that substance abuse is at least as prevalent among welfare recipients as non-recipients (Jayakody, Danziger, and Pollack, 2000;Jayakody and Stauffer, 2000). When present, mental health disorders and/or substance abuse problems affect the employment outcomes of welfare recipients .…”
Section: Methodsmentioning
confidence: 99%
“…2 As a result, support services to address mental health and substance barriers to employment have become common components of welfare-to-work strategies and are intended to improve the economic outcome of welfare recipients experiencing those barriers (Jayakody, Danziger, and Pollack, 2000;Metsch et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Using 1994-1995 data from the National Household Survey of Drug Abuse (NHSDA), Jayakody and colleagues found that 21% of welfare recipients who received cash assistance reported use of an illegal drug during the past year, compared to 13% of non-recipients. 202 Excluding marijuana, about 10% of welfare recipients reported use of some other illegal drug during the past year, compared to 7% of non-recipients, however, as the researchers caution these differences were not statistically significant. 203 Similarly, using 2002 data from the National Survey of Drug Use and Health-the successor to the NHSDA-Pollack and colleagues found that 22.3% of women TANF recipients aged 18-49 reported using illegal drug use during the previous year compared to 12.8% of women who did not receive TANF benefits.…”
Section: The Probability Of the Harm A National Estimatesmentioning
confidence: 97%
“…Moreover, women who smoke are more likely to have depressive symptoms or clinical depression (Morbidity and Mortality Weekly Review, 2002) and smoking is associated with central obesity in poor African American women (Office on Women's Health, 2001). Researchers estimate that 6% to 10% of women on welfare consume alcohol (Jayakody, Danziger, & Pollack, 2000). Also, women employed while receiving welfare (e.g.…”
Section: Overviewmentioning
confidence: 99%
“…Some researchers estimate that 6 to 10% of welfare recipients use alcohol (Jayakody, Danziger & Pollack, 2000), although other researchers suggest that the rates of alcohol use among welfare recipients may be inflated. Data is limited on alcohol use in African American women on welfare.…”
Section: Prevalence Of Health Risk Behaviorsmentioning
confidence: 99%